Efeito da ciclofosfamida sobre o desenvolvimento de germe dental do incisivo do camundongo. - Matheus, M. T. (1990)
Thirty six female mice were injected on the 12th day of the gestational period with 0.2 ml of distilled water (control group) or of an acqueous solution containing either 30 mg/Kg or 50 mg/Kg of body weight of cyclophosphamide (treated group). The animal were killed at 24, 48, 72, 96 and 120 hours after the injection and 3 days after birth. It was verified that cyclophosphamide interferes on the tooth germ development and that this effect is in directly ratio of the doses used.